2021
DOI: 10.3390/molecules26051272
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Potent Anti-Inflammatory Compounds (ROS Inhibitors) from Isonicotinic Acid

Abstract: In search of anti-inflammatory compounds, novel scaffolds containing isonicotinoyl motif were synthesized via an efficient strategy. The compounds were screened for their in vitro anti-inflammatory activity. Remarkably high activities were observed for isonicotinates 5–6 and 8a–8b. The compound 5 exhibits an exceptional IC50 value (1.42 ± 0.1 µg/mL) with 95.9% inhibition at 25 µg/mL, which is eight folds better than the standard drug ibuprofen (11.2 ± 1.9 µg/mL). To gain an insight into the mode of action of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Compound 76 was one of the most potent anti-inflammatory agents, with IC 50 of 1.42±0.1 µg/mL. 214 The antagonizing hormone glucocorticoid stimulates hepatic glucose synthesis while inhibiting insulinassisted glucose absorption in skeletal muscles and adipose tissue. 215 Glucocorticoidal stimulation, which is coordinated by 11β-HSD2 and 11β-HSD1 enzymes, is often used to measure glucocorticoid target-tissue activity.…”
Section: Anti-inflammatory Drugs and Active Compoundsmentioning
confidence: 99%
“…Compound 76 was one of the most potent anti-inflammatory agents, with IC 50 of 1.42±0.1 µg/mL. 214 The antagonizing hormone glucocorticoid stimulates hepatic glucose synthesis while inhibiting insulinassisted glucose absorption in skeletal muscles and adipose tissue. 215 Glucocorticoidal stimulation, which is coordinated by 11β-HSD2 and 11β-HSD1 enzymes, is often used to measure glucocorticoid target-tissue activity.…”
Section: Anti-inflammatory Drugs and Active Compoundsmentioning
confidence: 99%
“…Yaqoob et al. 65 synthesised novel scaffolds containing isonicotinoyl motif derivatives and screened for their in vitro anti-inflammatory activity. Results showed that compound 50 ( Figure 5 ) exhibited an exceptional IC 50 value (1.42 ± 0.1 µg/mL) with 95.9% inhibition at 25 µg/mL, which is eight folds better than the standard drug ibuprofen (11.2 ± 1.9 µg/mL) 65 .…”
Section: Recent Development In Anti-inflammatory Agentsmentioning
confidence: 99%
“…These medications are used to treat muscular and articular inflammatory diseases such osteoarthritis and rheumatoid arthritis. Yaqoob et al [17] created a class of strong anti-inflammatory drugs employing derivatives of Isonicotinic acid, such as pyridine. Figure 17 demonstrates the extremely high ROS-inhibitory activity of structures 77 and 79.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…Figure 17 demonstrates the extremely high ROS-inhibitory activity of structures 77 and 79. Compound 77 was determined to be the most effective with an IC50 of 1.4 g/ML [17] . In 2019, Kandasamy et al [18] reported that they have developed a chemical that suppresses inflammation by blocking nitric oxide (NO) production at a concentration of 26 micromolar (M).…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%